Syphilitic periostitis of the skull and ribs in a HIV positive patient. Issue 1 (11th November 2010) - Samarkos, Michael; Giannopoulou, Charis; Karantoni, Eleni; Papastamopoulos, Vassileios; Baraboutis, Ioannis; Skoutelis, Athanassios
Abstract : We report the case of a HIV and syphilis co-infected patient who presented with headache and rash and was found to have syphilitic periostitis. Our case illustrates a rare manifestation of early syphilis and presents the diagnostic dilemmas that can arise in HIV and syphilis co-infected patients.